Collagen: A review on its sources and potential cosmetic applications - Avila Rodríguez, María Isabela (2018)
Collagen is a fibrillar protein that conforms the conjunctive and connective tissues in the human body, essentially skin, joints, and bones. This molecule is one of the most abundant in many of the living organisms due to its connective role in biological structures. Due to its abundance, strength and its directly proportional relation with skin aging, collagen has gained great interest in the cosmetic industry. It has been established that the collagen fibers are damaged with the pass of time, losing thickness and strength which has been strongly related with skin aging phenomena [Col ageno para todo. 60 y m as. 2016. http://www.revista60ymas.es/InterPresent1/groups/revistas/documents/binario/ses330informe.pdf.]. As a solution, the cosmetic industry incorporated collagen as an ingredient of different treatments to enhance the user youth and well-being, and some common presentations are creams, nutritional supplement for bone and cartilage regeneration, vascular and cardiac reconstruction, skin replacement, and augmentation of soft skin among others [J App Pharm Sci. 2015;5:123-127]. Nowadays, the biomolecule can be obtained by extraction from natural sources such as plants and animals or by recombinant protein production systems including yeast, bacteria, mammalian cells, insects or plants, or artificial fibrils that mimic collagen characteristics like the artificial polymer commercially named as KOD. Because of its increased use, its market size is valued over USD 6.63 billion by 2025 [Collagen Market By Source (Bovine, Porcine, Poultry, Marine), Product (Gelatin, Hydrolyzed Collagen), Application (Food & Beverages, Healthcare, Cosmetics), By Region, And Segment Forecasts, 2014 – 2025. Grand View Research. http://www.grandviewresearch.com/industry-analysis/ collagen-market. Published 2017.]. Nevertheless, there has been little effort on identifying which collagen types are the most suitable for cosmetic purposes, for which the present review will try to enlighten in a general scope this unattended matter